Release Groups & The Scene: Re-Intermediation and Competitive Gatekeepers Online (Cinéma & Cie. Film and Media Studies Journal, 2017)
While recent years has witnessed the proliferation of new modes and methods of informal distribution, a certain sector of unauthorized media distribution, namely ‘The Scene’, has been subject to surprisingly little academic consideration. ‘The Scene’ is a collective title for several self-identi ed ‘release groups’ who collaborate to remove copyright protection from media artefacts (e.g. games, software, lms) and repackage them into ‘releases’ for distribution online. Despite assertions that the Scene is the source of ‘most’ pirate copies circulating online, the role these online gatekeepers play in selecting what is ‘released’ into unauthorized online distribution networks has yet to be thoroughly explored. As such, this paper will examine how the practices of The Scene intersect with the wider unauthorized distribution ecology and how they might act as both tastemakers and gatekeepers in an online context that is frequently perceived to be ‘free’, ‘open’ and untroubled by traditional intermediaries. In doing so, the paper will consider how the practices of the Scene are emblematic of the wider processes of re-intermediation that are being felt across the audio-visual industries.